A robust poly(N-acryloyl-2-glycine)-based sponge for rapid hemostasis. (12th June 2020) - Chen, Xinyu; Cui, Chunyan; Liu, Yang; Fan, Chuanchuan; Xiao, Meng; Zhang, Dongfei; Xu, Ziyang; Li, Yuan; Yang, Jianhai; Liu, Wenguang
Abstract : A robust sponge fabricated by bubble expanding in thermo-initiation polymerization and lyophilization demonstrates H-bonding strengthened compressive strengths, tunable liquid uptake capability and excellent hemostatic activity. Abstract : The development of a hemostatic sponge that can be used for treating both arterial hemorrhage and non-compressible bleeding remains a challenge. In this work, we propose the fabrication of a robust hemostatic sponge by a hydrogen bond strengthening and in situ bubble expanding strategy in thermo-initiation polymerization. A thickening agent, carboxymethyl cellulose (CMC), is incorporated into a hydrogen bonding N -acryloyl-2-glycine (ACG) monomer and an initiator, and vortexing generates air bubbles in the viscous liquid. Heating initiates fast polymerization, and meanwhile aids in expanding of bubbles, which results in the fixation of bubbles throughout the network, and the formation of porous hydrogels. Further lyophilization of the foaming hydrogels leads to the final generation of PACG/CMC sponges with robust compressive strengths due to the hydrogen bonding interactions of PACG. PACG/CMC sponges are shown to demonstrate a tunable liquid absorption ability, in vitro hemostatic ability, better hemocompatibility and cytocompatibility. In a rat liver injury model and a femoral artery injury model, the PACG/CMC sponge can significantly reduce the bleeding time and blood loss compared with gauze and commercial gelatin sponge because of the high blood absorption ability and effective concentration of blood coagulation factors. This PACG sponge holds promising potential as a hemostatic agent applicable in an emergency.